Synthesis and biological activity of new rhodanine-triazole conjugates with 2-(2,6-dichlorophenylamino)benzyl moiety in the molecules - Yu. L. Shepeta; O. M. Roman; I. O. Nektiehaiev; R. B. Lesyk (Zaporozhye State Medical University, 2020)
Molecular design of "drug-like" molecules based on the combination of a fragment of non-steroidal anti-inflammatory drug diclofenac with a pharmacologically attractive 1,2,4-triazole and 4-thiazolidinone "structural matrices" in one molecule is an effective approach in modern medical chemistry. Aim. Synthesis of new rhodanine-triazole hybrid molecules (conjugates) with 2- (2,6-dichlorophenylamino) benzyl moiety and evaluation of their biological activity. Materials and methods. The method of rhodanine-triazoles synthesis was elaborated. The structures of the synthesized compounds were confirmed by elemental analysis, NMR spectroscopy, and LCMS. The anti-exudative activity of the compounds was investigated in a rat carrageenan edema model, and the antitumor effect was studied in vitro at a concentration of 10-5 M on 60 cancer cell lines (DTP NCI Program). Results. Novel 2-{5-[2-(2,6-dichlorophenylamino)-benzyl]-4H-1,2,4-triazol-3-ylsulfanyl}-N-(4-oxo-2-thioxothiazolidin-3-yl)-acetamides and their 5-arylidene derivatives were synthesized/ Among these derivatives hit compounds with anti-inflammatory and anticancer activity against cell lines of melanoma, leukemia, non-small cell lung cancer, colon cancer, CNS cancer, ovarian cancer, renal cancer, and breast cancer were identified. Conclusion. The molecular design of rhodanine-triazole hybrid molecules based on diclofenac is an effective approach to the search for novel anti-inflammatory and antitumor agents.